2021
DOI: 10.1002/hsr2.432
|View full text |Cite
|
Sign up to set email alerts
|

Clinical spectrum, risk factors, and outcomes of children with laboratory‐confirmed influenza infection managed in a single tertiary hospital: A 6‐year retrospective cohort study

Abstract: Background Influenza is a highly contagious disease that causes severe illness each year. Data in the United Arab Emirates are scarce. Objectives To study the seasonality, morbidity, mortality rate, and comorbidities associated with confirmed influenza infection in a tertiary hospital in Al‐Ain city, UAE. Methods Retrospective study, from 2012 to 2017, of the electronic medical records in Tawam hospital, of children up to 15 years of age with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
1
0
0
Order By: Relevance
“…The frequency of signs and symptoms of influenza that we found largely support the results of previous work, but the frequencies of acute otitis media and pneumonia in this study are lower than the frequencies often reported in the literature [ 2 , 5 , 6 , 28 , 29 ]. This is partially because this study primarily examines non-hospitalized children, a population expected to be less severely ill than children in hospitalized cohorts [ 5–7 ].…”
Section: Discussionsupporting
confidence: 91%
“…The frequency of signs and symptoms of influenza that we found largely support the results of previous work, but the frequencies of acute otitis media and pneumonia in this study are lower than the frequencies often reported in the literature [ 2 , 5 , 6 , 28 , 29 ]. This is partially because this study primarily examines non-hospitalized children, a population expected to be less severely ill than children in hospitalized cohorts [ 5–7 ].…”
Section: Discussionsupporting
confidence: 91%